An Evaluation of University Students' Perceptions of Gender Violence-A Study of Its Prevalence in Southern Spain - Mercedes Osuna-Rodríguez; María Isabel Amor; Irene Dios (MDPI AG, 2023)
Discovering students' beliefs and values as regards gender violence is a fundamental factor when attempting to tackle this problem in the sphere of universities. This study presents the validation of a scale for university students' perceptions of gender-based violence, denominated as the Gender Violence Perception Scale (GVP-S). This scale measures the degree to which the aforementioned perceptions are influenced by gender, the university degree in which participants are enrolled, the type of school to which (i.e., private or state) they attended, and the level of education reached by their parents. The study was carried out with a sample of 1870 students at the University of Cordoba (Spain), and its results revealed that: (1) the GVP-S is well adjusted to and has the optimum psychometric properties for the sample studied, and (2) there are significant differences according to gender, the university degree being studied and the students' parents' education, but not the type of secondary education establishment attended. The conclusion that was reached was that it is necessary to carry out more research in this area, to provide preventative measures and training programs regarding gender violence to university students.